(untitled) (Scientific journal of the Fergana State University, 2024)
This article will focus on a topic that remains relevant at the moment, namely the methods of linking English lessons in higher education to the industry. The article also recognizes that the organization of industry classes is a requirement of modernity and that on the basis of decisions taken by the head of state, an Agency for the Popularization of Foreign Language Learning was created. The author gave recommendations on where to get professional texts and in what order to use them in the lesson, based on the opinions of foreign and Uzbek scientists. It was suggested that the main part of the resources of English lessons conducted in technical higher education are professional texts, and that in addition to the four goals pursued in English lessons, that is, practical, educational, educational and developmental, the fifth goal is also pursued professionally. The difference between the disciplines of general and special purpose English is explained on the basis of opinions in various literature. The article is enriched with various professional texts, and on its basis the features and requirements of professional texts are outlined.